Constraint Solving and Language Processing 7th International Workshop, CSLP 2012, Orléans, France, September 13-14, 2012, Revised Selected Papers - Duchier, Denys; Parmentier, Yannick; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The Constraint Solving and Language Processing (CSLP) workshop considers the role of constraints in the representation of language and the implementation of language processing applications. This theme should be interpreted inclusively: it includes contributions from linguistics, computer science, psycholinguistics and related areas, with a particular interest in interdisciplinary perspectives. Constraints are widely used in linguistics, computer science, and psychology. How they are used, however, varies widely according to the research domain: knowledge representation, cognitive modelling, problem solving mechanisms, etc. These different perspectives are complementary, each one adding a piece to the puzzle.
The Role of Universal Constraints in Language Acquisition -- Building and Exploiting Constraint-Based Treebanks -- An Account of Natural Language Coordination in Type Theory with Coercive Subtyping -- A Speaker-Referring OT Pragmatics of Quantity Expressions -- Modelling Language, Action, and Perception in Type Theory with Records -- Probabilistic Grammar Induction in an Incremental Semantic Framework -- A Predicative Operator and Underspecification by the Type Theory of Acyclic Recursion -- Ontology Driven Contextual Best Fit in Embodied Construction Grammar -- Describing Music with MetaGrammars -- Resolving Relative Time Expressions in Dutch Text with Constraint Handling Rules.
Keywords: Computer science; Software engineering; Logic design; Information storage and retrieval systems; Artificial intelligence; Computer Science; Mathematical Logic and Formal Languages; Logics and Meanings of Programs; Artificial Intelligence (incl. Robotics).; Software Engineering; Programming Languages, Compilers, Interpreters; Information Storage and Retrieval